Infarct volume as a predictor and therapeutic target in post-stroke cognitive impairment - Xu, Lingjia; Shan, Dan; Wu, Danling (Frontiers in Medicine, 2025)
Post-stroke cognitive impairment is one of the most common consequences of stroke, affecting more than half of stroke patients, especially in the geriatric population. Post-ischemic stroke cognitive impairment (PISCI) is particularly detrimental, as it can exacerbate a patient’s disability. Given that the severe consequences of adverse life outcomes are major contributors to disability and death among survivors of ischemic stroke, preventing stroke and PISCI remains a fundamental strategy for maintaining optimal brain health. Recent studies have extensively investigated the epidemiology, diagnosis, and management of PISCI. Nevertheless, significant gaps persist in our understanding of its pathophysiological mechanisms and potential therapeutic targets, which warrants further research. Factors such as baseline brain health, cerebral small vessel disease, and stroke characteristics (e.g., infarct location, severity, and morphology) have been associated with PISCI. However, its pathophysiology remains inadequately understood. Recent research suggests that infarct volume may serve as a novel indicator for predicting and managing PISCI. Thus, this review aims to expand our understanding of factors influencing PISCI and to elucidate its pathophysiological mechanisms. In particular, infarct volume has been proposed as a potential target and may play a critical role in predicting and managing PISCI. We advocate for improved and timely predictions of PISCI to enhance the quality of life for patients and reduce the economic and emotional burden on caregivers.